Business Network Analysis of Gurilem Crackers MSMEs In Cililin Sub-District, West Bandung Regency - Andi Sutisna; Resya Dwi Marselina; Pramia Andriana Putri (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
In order to mitigate the elevated unemployment rate in Indonesia, the community must investigate other business prospects, such as small and medium-sized enterprises (SMEs), exemplified by Gurilem Crackers. Gurilem Crackers, a small and medium-sized enterprise (SME), possesses a robust and established infrastructure encompassing business networks, production methods, marketing strategies, and financial resources. These elements contribute to the improvement of firm productivity and market competitiveness. The data gathering method employed is descriptive qualitative, including interviews and observations. This study examines the business network, production processes, marketing tactics, and finances of Gurilem Crackers SME, which Mang Teten owns in the Bongas hamlet. The research findings suggest that Mang Teten's company utilizes business networking by collaborating with Gurilem cracker suppliers, employs essential production tools, relies exclusively on word of mouth for Gurilem Cracker marketing, and achieves a monthly profit of Rp—1,236,000.00 with a profit margin of 8.9%.